18F-FDG-PET guided vs whole tumour radiotherapy dose escalation in patients with locally advanced non-small cell lung cancer (PET-Boost): Results from a randomised clinical trial. (April 2023) - Cooke, Saskia A.; de Ruysscher, Dirk; Reymen, Bart; Lambrecht, Maarten; Fredberg Persson, Gitte; Faivre-Finn, Corinne; Dieleman, Edith M.T.; Lewensohn, Rolf; van Diessen, Judi N.A.; Sikorska, Karolina; Lalezari, Ferry; Vogel, Wouter; et al.
Highlights: Multi-center trial testing two personalised radiotherapy dose-escalation strategies. 107 patients with stage II/III disease and a large primary tumour were randomised. 24 fractions escalated dose to the whole primary tumour or the PET-subvolume. Freedom from local failure rates were high (1-year > 90 %) in both arms. Unexpected increased rates of grade 5 events were seen in both arms. Abstract: Background and purpose: We aimed to assess if radiation dose escalation to either the whole primary tumour, or to an 18 F-FDG-PET defined subvolume within the primary tumour known to be at high risk of local relapse, could improve local control in patients with locally advanced non-small-cell lung cancer. Materials and methods: Patients with inoperable, stage II-III NSCLC were randomised (1:1) to receive dose-escalated radiotherapy to the whole primary tumour or a PET-defined subvolume, in 24 fractions. The primary endpoint was freedom from local failure (FFLF), assessed by central review of CT-imaging. A phase II 'pick-the-winner' design (alpha = 0.05; beta = 0.80) was applied to detect a 15 % increase in FFLF at 1-year. ClinicalTrials.gov :NCT01024829. Results: 150 patients were enrolled. 54 patients were randomised to the whole tumour group and 53 to the PET-subvolume group. The trial was closed early due to slow accrual. Median dose/fraction to the boosted volume was 3.30 Gy in the whole tumour group, and 3.50 Gy in the PET-subvolume group. The 1-year FFLF rate was 97 % (95 %CI 91–100) in whole tumour group, and 91 % (95 %CI 82–100) in the PET-subvolume group. Acute grade ≥ 3 adverse events occurred in 23 (43 %) and 20 (38 %) patients, and late grade ≥ 3 in 12 (22 %) and 17 (32 %), respectively. Grade 5 events occurred in 19 (18 %) patients in total, of which before disease progression in 4 (7 %) in the whole tumour group, and 5 (9 %) in the PET-subvolume group. Conclusion: Both strategies met the primary objective to improve local control with 1-year rates. However, both strategies led to unexpected high rates of grade 5 toxicity. Dose differentiation, improved patient selection and better sparing of central structures are proposed to improve dose-escalation strategies.